Penerapan Analisis Runtun Waktu pada Peramalan Penjualan Produk Organik menggunakan Metode Moving Average dan Exponential Smoothing - Irfan Ardiansah; Irsyad Fauzi Adiarsa; Selly Harnesa Putri; Totok Pujianto (The University of Lampung, 2021)
The purpose of this study is to answer the problem of procurement of goods and minimize goods reaching expiration due to too long storage time, then as a provider of information about the forecasting system at Warung Sehat 1000 Kebun, then to predict sales of goods at Warung Sehat 1000 Kebun and identify how many goods that have been sold. This research uses a quantitative approach. The data used in this study is sales data for 2 (two) months with 30 lines of data and a total of 3 types of goods studied, namely sales data of pakcoy, cocofresh and free-range chicken eggs. The method used starts from data collection, forecasting calculations, forecasting testing, forecasting selection, and forecasting application. The forecasting methods used are moving average and exponential smoothing, by testing the mean absolute deviation, mean square error, and standard deviation. Forecasting results yielded outputs for pakcoy products as much as 1583.33 grams, for cocofresh products as many as 11 pcs and for chicken eggs as many as 9 pcs. Keywords: exponential smoothing, forecasting examination, time series data, moving average